[PP.04.18] COMPARISON AMONG DIFFERENT ELECTROCARDIOGRAPHIC CRITERIA FOR LEFT VENTRICULAR HYPERTROPHY: RETROSPECTIVE ANALYSIS OF A LARGE COHORT OF ADULT OUTPATIENTS WITH HYPERTENSION. (September 2017) - Tocci, G.; Costanzi, V.; Gallo, G.; Simonelli, F.; Attalla, N.; Figliuzzi, I.; Presta, V.; Citoni, B.; Battistoni, A.; Ferrucci, A.; Volpe, M.
Abstract : Objective: Introduction. Conventional 12-lead electrocardiogram (ECG) should be performed in all patients with hypertension (HT) in order to evaluate the presence of cardiac organ damage (OD), namely left ventricular hypertrophy (LVH), although different criteria are available. Design and method: Aim. To evaluate LVH prevalence according to conventional and new ECG criteria in a large cohort of adult hypertensive outpatients. Methods: All patients underwent conventional 12-lead ECG, BP assessment and comprehensive evaluation of individual global cardiovascular risk profile according to 2013 ESH/ESC guidelines. The following ECG criteria for LVH were applied: 1) Sokolow–Lyon index: >3.5 mV; 2) Cornell Voltage Index: men >2.4 mV; women >2.0 mV. In addition, positive/negative amplitude of all ECG leads was calculated in all included outpatients. Study population was stratified into three groups: 1) treated controlled HT; 2) treated uncontrolled HT; 3) resistant HT. Results: Results. From an overall population sample of 1, 979 adult individuals, we selected 1, 566 hypertensive outpatients, among whom 560 (35.8%) were treated controlled, 613 (39.1%) were treated uncontrolled, and 393 (25.1%) had resistant HT. No significant difference was found for LVH prevalence according to Sokolow-Lyon criterion, whereas its prevalence increased from controlled (7.7%) to uncontrolled (9.4%) towards resistant (14.%) HT according to Cornell Voltage criterion (P < 0.040). Cornell Voltage and Product showed a trend toward increase from the first to the latter group. Among various ECG leads, only aVL amplitude showed a progressive and significant increase from controlled (5.7 ± 3.8 mV) to uncontrolled (6.0 ± 3.4 mV) towards resistant (6.7 ± 3.7 mV) HT, as well as positive correlation with clinic systolic BP (Pearson r: 0.158; P < 0.001), 24-hour systolic BP (r: 0.133; P = 0.007), LVMi (r: 0.206; P < 0.001), and LVMh^2.7 (r: 0.239; P < 0.001). Conclusions: Conclusions. Measuring aVL amplitude might represent a simple, easy and cost-effectiveness way to assess the presence of cardiac OD in adult outpatients with different degree of hypertension.